Governança corporativa, princípios globais de contabilidade gerencial e código de ética empresarial de empresas brasileiras de capital aberto - Correia, Thamirys de Sousa (2018)
The objective of the research was to verify the relations of Corporate Governance with the Global Principles of Managerial Accounting (PGCG) and the Code of Business Ethics (CEE) of Brazilian companies. As for the methodology, data were collected from companies that traded shares in Brazil, Bolsa e Balcão (B3) through the Comdinheiro database, reference forms, company website, CVM website, B3, management reports, annual reports, standardized financial statements, sustainability reports and codes of ethics or business conduct. To do so, regarding the dependent variables, indexes was constructed to represent the PGCG (IPGCG) and indexes referring to the CEE (ICEE). The independent variables are the Board of Directors (Council size, Chairman's gender, Independence, Chairman/CEO, Age, and Council Meetings), Property Structure and Control (Annual average of the percentage of total shares of the largest shareholder; and, Percentage of common shares of the largest shareholder) and Remuneration of Executives (Total Remuneration, Fixed Remuneration and Variable Remuneration of the Executive Board). In order to identify the relationships between Corporate Governance and IPGCG, regression models were estimated on panel data of fixed effects with robustness, and random effects (period from 2010 to 2016). On the other hand, to identify the relationships between Corporate Governance and ICCE, the technique used was the cross-section (year of analysis was 2016) and the chosen model was the Ordinary Minimum Square (OLS). The results show that all six indicators referring to the Board of Directors are explanatory factors of IPGCG, especially independence, with the highest coefficients: 20,58% (Level 1), 12,92% (Level 2) and 7,23% (New Market). Thus, an independent board positively influences the managerial information that made up the IPGCG, generating and preserving value for the selected companies. Whereas, the Property Structure had a negative impact on the IPGCG, although only for the sample of companies listed in the Level 2 segment and with a poorly representative coefficient. Fixed remuneration also explains the IPGCG, which is why it is the most usual means of payment for executives in Brazil. In addition, the size of the council, the independence and the number of meetings explain in a positive way the ICEE, as well as the cumulation of the positions of president of the board and CEO influences in a negative way in the ICEE, that is, negatively impacting in the CEE, that by its turn represents the management, the characteristics of the business and the ethical stance of managers and senior executives.